The Importance of Cotton Crop in the World and the Impact of the Upland Case DS 267/45 at WTO Dispute Settlement Body - Albertini, Maria de Lourdes Monteiro (Virtuajus, 2017)
Cotton is one of the major international commodities, playing a fundamental role for many countries, mainly for the less developed countries, and even developed countries maintain certain regions where this crop is just as important as it is for the poorer ones, such as the Mississippi Delta in the United States of America, whose local economy depends strongly on cotton plantations. The research seeks to analyze the case of the upland cotton (DS267/45) presented before the Dispute Settlement Body of the World Trade Organization, related to the United States of America subsidies Act (the Farm Bill of 2002). Initially the research focuses on the role of cotton in the US economy, its production areas and the social aspects involved, trying to glimpse at some of the reasons that led this country to strongly defend the financing of the sector. Secondly, the research evaluates the importance of cotton to several countries, rebuilding historically this culture, besides seeking to understand the current importance of cotton for economic and social sustainability of countries like West Africa, India, and especially, Brazil. The text also analyzes the relationship between a cotton culture and slave labor, as well as the violence and precarious working conditions associated with African Americans. All research will be developed under the theories that study the multilateralism trade in the international arena.